LOOK, LOOK! THIS SHRINE IS LEAKING RED “MENSTRUAL ACTIVISM IN NINA PAGALIES’ GRAPHIC TEMPLES” - Katyal, Aishwarya; Jain, Neha (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Menstruation is a physiological phenomenon that has long been associated with taboos and myths that justify women’s exclusion from religious ceremonies and the public realm. Many cultures around the world consider menstruating women as unholy and polluting, often associating them with filth that must stay beyond the threshold of shrines and places of worship. Owing to the negative attributes associated with menstruation, the equation between women’s bodies and divinity gets problematized leading to their polarised conception. Such beliefs culminate into sexist practices that often undermine women’s rights and freedom and become instruments of perpetuating gender-based violence against them. The controversy of Sabarimala Temple in India stands as testimony to the above statement. This paper explores graphics from a collection titled ‘Temples’ by a German illustrator, Nina Pagalies, anthologized in The Elephant in the Room: Women Draw their World. Her work, Temples, explore varied experiences and attributes of female sexuality that are beautifully dovetailed to the idea of religion and purity by depicting women’s bodies as shrines and temples, thus reconciling the otherwise polarised view of female sexuality and the divine. This paper unravels how the Pagalies’ visuals subvert the notion of dirt and impurity associated with menstruation to support the narrative that rather celebrates it. It undertakes a semiotic analysis of the ‘gendered blood’ and other motifs to understand how these visuals are transgressive. Subsequently, the paper closes with the view that the illustrations valourize the ‘female blood’ and debunks patriarchal modes of representation by carving a democratic vista for feminine expression advocating the permission of menstruating females into temples.